Jurgen Habermas: Kritik atas Rasionalisasi dan Materialisme Sejarah - Agus Darmaji (Refleksi: Jurnal Kajian Agama dan Filsafat, 1999)
In this article, Habermas's thought will be discussed in three parts. First, the continuity and discontinuity of Habermas's thought with his predecessors will be examined. Second, a general overview will be provided of the relationship or differences in the paths of Marxist thought in general and Habermas as a thinker who adheres to Marxist thought. Third, the discussion will delve into the theoretical realm concerning Habermas's central concepts that distinguish him radically from Marxist and neo-Marxist thought in general.